Case 3706: Trochus (Osilinus ?) capillaceus Philippi, 1849 (currently Cantharidus capillaceus; Mollusca, Gastropoda, Trochoidea): proposed conservation of the specific name - Marshall, B A; Beu, A G; Ponder, W F; Spencer, H G; Walton, K; Willan, R C (Bulletin of Zoological Nomenclature, 2017)
The purpose of this application, under Article 23.9.3 of the Code, is to conserve the specific name of the well-known species Cantharidus capillaceus (Philippi, 1849), a common marine gastropod from southern New Zealand and Macquarie Island. The name is threatened by the senior subjective synonym Trochus episcopus Hombron & Jacquinot, 1848 which has been mentioned very rarely since its first publication. Precedence of the name Trochus capillaceus Philippi, 1849 over Trochus episcopus Hombron & Jacquinot, 1848 is proposed.
Keywords: Nomenclature; taxonomy; Mollusca; Gastropoda; Trochoidea; Cantharidus; Micrelenchus; Photinula; Trochus; Trochus capillaceus; Trochus episcopus; New Zealand